Imagined reality: Urban space and Sui-Tang beliefs in the underworld - Sun, Yinggang (Studies in Chinese Religions, 2015)
Chang’an 長安, the political, economic, and cultural center of the Sui-Tang period, is of great scholarly significance for the study of medieval Chinese political, religious, and cultural change. The scholarly study of Chang’an has already achieved research advances focused on the study of urban space, as well as politics, religion, ritual, and literature as they were manifested in the space of the urban wards in the process of (larger) social transformations. There are a relatively large number of contemporary studies that discuss the concrete, actual urban world. However, in reality there are abundant sources on Sui-Tang Chang’an’s history that provide information regarding the spiritual world of Chang’an. The spiritual or mental realm also comprises an important aspect of historical research that must not be overlooked. In addition to the actual, concrete world, the mental realm of Chang’an’s clerical and lay elites, as well as that of the mass of the populace, was also reflected in Chang’an’s urban spaces. On the level of life and death, the minds of Chang’an’s residents were preoccupied with an underworld. Between the realms of ‘darkness’ 幽 (the underworld 冥界) and ‘light’ 明 (the realm of the living 生界) there existed mechanisms for mutual communication, and thus information from the underworld could be conveyed to the realm of the living.